Animal bone material from Lublin-Volhynia Grave 8 at Site 2 in Książnice, Pacanów commune, Świętokrzyskie Province - Makowicz-Poliszot, Danuta (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2014)
The article presents the results of zoological analysis of animal bones (45 pieces) from Grave 8 (Feature 3/08, the Lublin-Volhynia culture) discovered in 2008 in Książnice, Site 2. The identified remains (25 pieces) come from goats/sheep Capra hircus L./Ovis aries L. (Table 1).
Zwierzęcy materiał kostny z grobu 8 kultury lubelsko-wołyńskiej ze stanowiska 2 w Książnicach, gm. Pacanów, woj. świętokrzyskie
Keywords: animal bones; Lublin-Volhynia culture; zoological analysis